Harmoni Sosial Membentuk Interaksi Sosial Agama Islam dan Agama Hindu: Social Harmony Shapes Social Interaction Between Islam and Hinduism - Miftahul Rezki (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2025)
Social interactions between Muslims and Hindus involve the convergence of different values, norms, and customs among followers of each religion, which has the potential to trigger problems in community life. Conflicts between the beliefs of followers of each religion occur in various regions. However, in the reality of these marriages, this is not a reason for the community in Laccoling. This study aims to describe and analyze the social interaction between Muslims and Hindus at weddings in Laccoling, Parepare City. The research method used a qualitative approach with descriptive research. Data collection techniques included observation, interviews, and documentation. The data analysis techniques used were data reduction, presentation, and conclusion drawing. The results of the study show that the form of social interaction that occurs at weddings in Laccoling is physical interaction, such as associative interaction, cooperation at weddings in Laccoling, and accommodation, which shows that the community demonstrates a pluralistic attitude of mutual respect for each other's religious rituals. Furthermore, in the interaction between the two communities, which shows the life of the Muslim and Hindu communities, there is social exchange in greeting, congratulating, and praying for each other. This interaction always occurs because